2019
DOI: 10.1590/s0102-865020190070000006
|View full text |Cite
|
Sign up to set email alerts
|

Protective roles of Pyracantha fortuneana extract on acute renal toxicity induced by cadmium chloride in rats

Abstract: Purpose:To investigate the protective roles of pyracantha fortune fruit extract (PFE) on acute renal toxicity induced by cadmium chloride (CdCl2) in rats.Methods:Rats were pretreated with PFE and consecutively injected with CdCl2 (6.5 mg/kg) for 5 days.Results:The concentration of Cd, kidney weight, malondialdehyde (MDA), and nitric oxide (NO) production were remarkably increased in CdCl2 group as well as the levels of plasma uric acid, urea, and creatinine (P < 0.001). However, the body weight and glutathione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…However, due to minor changes in serum creatinine level in cadmium-treated animals, it can be concluded that this metal is able to cause moderate to mild renal failure. In line with our findings, the destructive effects of cadmium on renal tissue have been reported in several studies (19,20). This evidence might be attributed to the alterations in the GFR, the threshold of tubular re-absorption, and renal blood flow.…”
Section: Discussionsupporting
confidence: 92%
“…However, due to minor changes in serum creatinine level in cadmium-treated animals, it can be concluded that this metal is able to cause moderate to mild renal failure. In line with our findings, the destructive effects of cadmium on renal tissue have been reported in several studies (19,20). This evidence might be attributed to the alterations in the GFR, the threshold of tubular re-absorption, and renal blood flow.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies proved that Cd could lead to chronic kidney disease and bone injury [ 5 ]. After ingestion of contaminated water and food by a human or animal, Cd primarily aggregates in the form of Cd-metallothionein complex in the liver and kidneys, and its turnover rate is excessively slow, which can disrupt the stability of essential metals such as zinc (Zn) and cuprum (Cu), reduce the capacity of cells to purge reactive oxygen species (ROS), cause oxidative stress and inflammation, and ultimately undermine organ function [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plant extracts were also found to exert wide protective effects against the third most dangerous heavy metal cadmium, with the results being confirmed by in vitro studies with using murine hepatocytes [ 3 ]. Additionally, an animal study showed the involvement of the Nrf2/Keap1 pathway into the protective action of Pyrantha fortuneana extract as the plant material, given both alone and coadministered with cadmium caused a significant increase in expression of Nrf2 and decrease in expression of Keap1 in the kidneys of rats vs. the control and Cd-exposed group, respectively [ 12 ].…”
Section: The Protective Properties Of Plant Preparations Against Tmentioning
confidence: 99%
“…The application of plant protection products has made another contribution to environmental contamination [ 6 9 ]. As it is not possible to improve the situation immediately, many people, i.e., industrial workers or farmers are still exposed to harmful substances like heavy metals [ 4 , 10 12 ], organic chemicals (e.g., CCl 4 ) [ 13 , 14 ], or pesticides and plant growth regulators [ 8 , 15 ]. Another problem results from introducing plenty of new pharmaceutical agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation